Visual detection and differentiation of porcine epidemic diarrhea virus wild−type strains and attenuated vaccine strains using CRISPR/Cas13a-based lateral flow strip - Yin, Dongdong; Yin, Lei; Guo, Hao; Wang, Jieru; Shen, Xuehuai; Zhao, Ruihong; Pan, Xiaocheng; Dai, Yin (Frontiers in Cellular and Infection Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) is an enteric coronavirus that causes acute watery diarrhea and vomiting in unweaned piglets. Infections result in high mortality and serious economic losses to the swine industry. PEDV attenuated vaccine does not completely protect against all mutant wild-type strains, and PEDV infection can periodically occur. A sensitive, accurate, and simple detection method for PEDV is needed to reduce the occurrence of the disease. In this study, the CRISPR/Cas13a system was combined with recombinase aided amplification to develop a rapid diagnostic method to distinguish PEDV wild-type strains from attenuated vaccine strains. The method is based on isothermal detection at 37°C. The results are used for visual readout. The assay had high sensitivity and specificity, with a detection limit of 101 copies/μL for the gene of interest, and no cross-reactivity with other pathogens. The Cas13a detection worked well with clinical samples. This visual, sensitive, and specific nucleic acid detection method based on CRISPR/Cas13a should be a powerful tool for detecting PEDV.